1980
DOI: 10.1097/00000658-198002000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Healing of Skin Wounds Caused by Burn and Freeze Injuries

Abstract: Circular, full-thickness dermal burn- and freeze-produced wounds were produced in rats to compare the difference in healing between the two types of thermal injuries. Contraction did not occur in wounds (n = 30) caused by freezing, while burn wounds (n = 30) contracted to less than one-third of original size by 21 days after injury. If the centers of the freeze-produced wounds (n = 12) were excised, contraction would then occur and proceed at the same rate as an open wound. Histologically, the degree of initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 6 publications
2
58
0
Order By: Relevance
“…Healed skin at these sites is rough and wrinkled. 49 Studies to determine whether collagen contraction could play a similar role in photoaged skin are in progress.…”
Section: Discussionmentioning
confidence: 99%
“…Healed skin at these sites is rough and wrinkled. 49 Studies to determine whether collagen contraction could play a similar role in photoaged skin are in progress.…”
Section: Discussionmentioning
confidence: 99%
“…PKC-Ī“ has been reported to play a major role in initiating and sustaining cell migration (Andre et al, 1999;Keller et al, 2000;Kruger and Reddy, 2003;Li et al, 1980), and in tumorcell metastasis (Kiley et al, 1999). The signaling pathway involving both PKC-Ī“ and RhoA has been implicated in mediating regulation of cell motility downstream of other types of cell surface receptors, such as the leukotriene D 4 , lysophosphatidic acid and bombesin receptors (Barry and Critchley, 1994;Massoumi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The result is that the extracellular matrix and scaffold structure of the nerves and vessels remain intact, allowing the affected axon/myelin sheath or vascular cells to regenerate and repair the injury site. In comparison, heat lesions have been found to not only destroy cells but also disrupt the structural matrix, resulting in a narrower therapeutic window [33][34][35]. A recent study [36] demonstrated that following a traumatic peripheral nerve injury, the regenerated myelin sheath was thinner and exhibited a decreased intermodal length.…”
Section: Safety Of Cryoneurolysismentioning
confidence: 99%